THE EMERGENCE OF EARLY KINDOMS IN SOUTH SULAWESI: A Preliminary Remark on Governmental Contracts from the Thirteenth to the Fifteenth Century - Abidin, Andi` Zainal; Aprasing, Andi (Journal of Humanity, 2014)
Pactum subjectionis or governmental contract is a covenant or compact between the ruler and the ruled envisaging their mutual rights and responsibilities [Abidin 1971:159; Harvey 1974:18; Riekerk quoting Catlin 1969:12]. Among the early states discussed by various scholars, e.g., Claesen and Skalnik (1978), Geertz (1979), Selo Soemardjan (1978), Coedes (1967), Hall and Whitmore (Aeusrivongse 1979), Reid and Castles (Macknight 1975), none subscribed to the practice of governmental contracts, except Bone in South Sulawesi. Despite its uniqueness, to my knowledge nothing has been written on the pactum subjectionis of early kingdoms on South Sulawesi, nor has any research been undertaken on this subject. This paper discusses the formation of main kingdoms in South Sulawesi and especially the governmental contract in the so-called Cappagalae (he big threeÃ¢â¬âLuwuâ, Bone and Gowa); two members of Tellumpoccoe (the three allied kingdoms in 1592), that is, Wajoâ and Soppeng; and a petty kingdom already known in the I La Galigo Epic Cycle, Cina, later called Pammana. Examples of such govermental contract are found at the beginning sections of historical chronicles (Lontaraâ attoriolong). Usually the very first parts of the chronicles contain a political myth which explains the origin of a dynasty as founded by a king or queen descending from heaven. Thus prior to the emergence of kingdoms in South Sulawesi, the first king called To Manurung (lit. He who came from the sky) had to make a contract with the representatives of the people called Ulu Anang or Matoa (Bugis)orKasuwiang(Makassar).